How did regulation and market discipline influence banking distress in Europe? : Lessons from the global financial crisis - Oliveira, Vitor Branco (2022)
Purpose – This paper aims to examine the relationship between regulation, market discipline and banking distress. Design/methodology/approach – To address the empirical question put forward above, a multivariate logit model is applied to an international sample of 586 banks from 21 European countries in the period between 2000 and 2012. To give robustness to the results, different variables have been used to test the role played by market discipline and regulation as well as an alternative methodology known as duration/survival analysis. Findings – It can be found that market discipline is a good indicator in signalling banking distress, that is, market discipline has penalized more banks with a higher likelihood of being in distress. Nonetheless, as broadly acknowledged, market discipline was not sufficient per se to avoid banking distress in Europe. With regard to regulation, this paper evidences that the adoption of other regulatory measures beyond the simple transposition of changes occurred in the EU Directives such as borrowerbased measures and limits on pre-emptive exposures’ concentration, have contributed toward reducing the probability of distress of EU banks, showing that the introduction of this kind of measures was necessary and relevant. In addition, in this paper, it can be found that the NPL ratio, size, capital (including the well-known regulatory capital ratio, as well as the novel leverage ratio which discards the risk weights present in the former one) and liquidity are good indicators of banking distress which lead us to conclude that the new regulatory framework known as Basel III is on the right path to mitigate the probability that a new banking crisis similar to the last one takes place again. Research limitations/implications – The first limitation regards the period of time chosen, that is, from 2000 to 2012, empirically neglecting, to some extent the important regulatory changes occurred after the aforementioned period. Nonetheless, as mentioned in the Data and Methodology section, the period ends in 2012 because it is difficult to flag a reasonable number of banks’ bailouts afterwards, to properly run the type of model used in this paper. The second limitation is the fact that the possible changes in the risk management and risk assessment by institutions and in the behaviour of investors, acknowledge as weak and inappropriate before the on-set of the global financial crisis, albeit very relevant, are not in the scope of this paper.